2007
DOI: 10.1002/art.22422
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4 regulates proteoglycan‐induced arthritis by specifically suppressing the innate immune response

Abstract: Objective. Interleukin-4 (IL-4) is an antiinflammatory cytokine that inhibits the onset and severity of proteoglycan-induced arthritis (PGIA). To distinguish the role of IL-4 in the innate immune response versus the adaptive immune response, we generated mice with a specific deletion of the IL-4 receptor ␣-chain (IL-4R␣) in macrophages and neutrophils.Methods. To obtain mice in which IL-4R␣ is deleted in macrophages and neutrophils, we inter- Conclusion. These findings indicate that IL-4 functions as a major a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
(38 reference statements)
2
26
2
1
Order By: Relevance
“…These studies, however, did not directly address the cell population targeted by IL-4. Consistent with our results, Cao et al showed that IL-4Rα signaling in myeloid cells indeed has a potent anti-inflammatory activity in the proteoglycans-induced arthritis model (32). The IL-4Rα forms a heterodimer with either the common cytokine receptor gamma chain (γ c /CD132) or IL-13Rα1 (CD213a1), making type 1 and 2 IL-4R, respectively.…”
Section: Resultssupporting
confidence: 92%
“…These studies, however, did not directly address the cell population targeted by IL-4. Consistent with our results, Cao et al showed that IL-4Rα signaling in myeloid cells indeed has a potent anti-inflammatory activity in the proteoglycans-induced arthritis model (32). The IL-4Rα forms a heterodimer with either the common cytokine receptor gamma chain (γ c /CD132) or IL-13Rα1 (CD213a1), making type 1 and 2 IL-4R, respectively.…”
Section: Resultssupporting
confidence: 92%
“…Tissue repair Increase of extracellular matrix remodelling and fibrogenesis Gratchev et al (2001) m Angiogenesis Goerdt et al (1993), Kodelja et al (1997) Modulation of inflammation mAnti-inflammatory cytokines kPro-inflammatory cytokines Modulation of the IL-27R Bonder et al (1998), Cheung et al (1990), Fenton et al (1992), Ruckerl et al (2006), Schebesch et al (1997), and Turnbull et al (2006) Protection of the host from unwanted inflammation during Pathology Placenta, lung Rheumatoid arthritis Psoriasis Alzheimer's disease Autoimmune encephalomyelitis Cao et al (2007), Colton et al (2006), Djemadji-Oudjiel et al (1996), Finnegan et al (2002), Goerdt et al (1993), Ponomarev et al (2007), and Szekanecz et al (1994) Ag presentation m MHCII expression Cua and Stohlman (1997) Recognition and uptake of glycoproteins and cancer cells Ichii et al (2000) and Kawakami et al (1994) Cheung et al, 1990). Moreover, AAMF selectively increase production of macrophage-derived chemokine (MDC) and thymus and activation-regulated chemokine (TARC), inducing recruitment of antigen presenting cells to the site of inflammation (Bonecchi et al, 1998;Mantovani et al, 2000).…”
Section: Role Referencementioning
confidence: 98%
“…Production of TGFb1 by alternatively activated macrophages has been documented (29), and the cells have been implicated in tissue repair and remodeling (30) and in protection of the host from damaging inflammation during pathology (31,32). In the context of pneumococcal nasopharyngeal colonization, they may limit inflammation to prevent tissue damage and thus promote prolonged carriage.…”
Section: Discussionmentioning
confidence: 99%